From Silent Ruins to Resilient Cultural Landscapes. Rethinking Heritage, Ecology, and Transformation in the Campi Flegrei case study - Castigliano, Marica; Attademo, Anna; Simioli, Maria (Contesti. Città, territori, progetti, 2026)
The paper explores the interplay between cultural landscapes and ecological systems, by adopting resilience as a unifying concept that bridges the preservation of heritage with sustainable and adaptive urban and territorial transformations. This approach has been developed in the research project carried out by DiARC (UNINA) within the PNRR Extended Partnership n.5 – Spoke 1. The focus is on "Campi Flegrei: a highly vulnerable area due to structural factors, given its volcanic nature, and the extractive use of resources where widespread historical assets and archaeological ruins emerge within the settlement fabric, often difficult to access, constantly exposed to risks, and experiencing degradation and abandonment. The research explores the interdependence between ecological-environmental values, history, communities, and ordinary landscapes through mapping activities and photographic campaigns for the activation of heritage communities as a factor of resilience. This allows the study to reveal a place-specific resilience with the aim of developing strategies that shift the role of archaeological ruins within the city - from static objects and barriers to contemporary transformation, to catalysts of resilient change.